Copeptin, myeloperoxidase and pro-adrenomedullin for acute coronary syndrome in patients with chronic kidney disease. (September 2019) - Pek, Jen Heng; Fook-Chong, Stephanie Man Chung; Choo, Jason Chon Jun; Tan, Carol Hui Chen; Lin, Ziwei; Chan, Choong Meng; Yeo, Chin Pin; Lim, Swee Han
Objectives: Copeptin, myeloperoxidase and pro-adrenomedullin have emerged as potential biomarkers for diagnosis and prognosis of acute coronary syndrome (ACS). However, their applicability in patients with chronic kidney disease (CKD) remains unknown as these patients were excluded from previous studies. Our objective was to determine the superior novel cardiac marker to predict 30-day and six-month adverse cardiac events (ACEs) defined as cardiac-related death, myocardial infarction and ventricular fibrillation. Methods: A prospective observational study was carried out. Patients were included if they presented to the emergency department with symptoms suggestive of ACS and had CKD as defined as a serum creatinine of more than 130 µmol/l. Copeptin, myeloperoxidase and pro-adrenomedulin assays were performed. Occurrence of ACE was traced from review of the patients' case records and the registry of deaths. Results: A total of 724 patients were recruited: 60.6% were male and 68.6% were Chinese. The median age was 67 years. Among those recruited, 88.3% had CKD stages 4 and 5, with 33.5% on dialysis. The rates of ACE at 30 days and six months were 15.1% and 21.7%, respectively. All readings of the three biomarkers were not significantly different in patients with ACE compared with those without both at 30 days and six months. The areas under the curve for copeptin, myeloperoxidase and pro-adrenomedullin were 0.53, 0.50 and 0.45, respectively ( p > 0.05). Conclusions: The poor performance of the biomarkers may be attributable to lack of specificity for ACS, as elevated levels could be from other causes in CKD patients. Routine testing cannot be recommended.